Analysis of vegetable market chain in Dugda Woreda, east Shoa Zone, Oromia Region, Ethiopia - Setegn, D. (Addis Ababa University, 2015)
This study is aimed at assessing vegetable market chain in Dugda Woreda, Oromia Region of Ethiopia focusing on tomato and onion products. Irrigated vegetable production is increasing with population growth and changes in consumption habits in Ethiopia creating business opportunity for many actors along the market chain, despite number of production and marketing constraints. Analysis of marketing performance of vegetable plays an important role in an ongoing or future market development plan. This study aimed at analyzing the market chain of vegetable for Dugda Woreda with the specific objectives of: identifying the key vegetable marketing actors and channels; examining market structure of major actors; assessing the market performance for key vegetable marketing actors and channels by quantifying costs and profit margins; and identifying key production and marketing constraints and opportunities faced by smallholders. The data was generated by household survey using a pre-tested structured questionnaire, key informant interview, focus group discussions, semi structured questionnaires and checklists. This was supplemented by secondary data collected from different published and unpublished sources. The data analyzed using SPSS version 20 and summarized into descriptive formats such as frequencies, percentages, means and standard deviation. Besides, Structure, Conduct and Performance (SCP) model employed to evaluate the structure and performance of vegetable market. The study finding shows that vegetable market chain actors are broadly classified into three: input suppliers; direct market actors (producers, brokers, farmer traders, wholesalers, retailers and consumers); and enablers (extension service providers & credit providers). Vegetable producers sell their products to different market intermediaries and final consumers. About five vegetable marketing channels were identified. The total amount of vegetable that was transacted through these marketing channels in 2014/15 was 32,010 quintals. Channel II was found to be the dominant marketing channel in terms of volume of vegetable supply, where about 23,752 quintals of vegetable (74.2% of the total vegetable) was supplied to the market. Channel III was the second dominant market supplier, where about 6,786 quintals of vegetable (21.2%) supplied through this channel. The study result also shows that the total gross marketing margin was 30% with producer participation margin of 70%. The market intermediaries incurred different marketing costs such as packing, sorting, transportation, loading and unloading. Central wholesalers obtain relatively highest profit in channel II and III, which amounted to Birr 204,827 and 58,675, respectively. The study result signifies that the first four largest volumes of vegetable purchased by traders (CR4) constitute 50% of market share, which indicates the market structure for vegetable is strongly oligopolistic. OLS regression results also revealed that there are economies of scale for wholesalers at Meki market, which clearly indicates the presence of barrier to entry/exit for wholesalers in the market. Opportunities identified for vegetable production include: existence of groundwater, convenient agro-ecology and ideally appropriate for agro-processing industries. On the other hand, challenges recognized for vegetable market chain includes: oligopolistic market structure, absence of storage facilities, soil salinity, overutilization of inputs (fertilizers), increasing cost of inputs, lack of improved seeds and chemicals (insecticides and fungicides), price fluctuation, and high market involvement of brokers. Policy implications drawn from the study findings necessitate legalizing and supporting actors in the local vegetable markets, creating access to accurate and regular market information and technical support to producers on crop diversification.